Antibacterial activity of copper-decorated CeO2 nanoparticles and preparation of antifouling polyethersulfone surface - Lokman Şener; Sadin Özdemir; M. Serkan Yalçın; Mehmet Gülcan; Nadir Dizge (Heliyon)
Cerium oxide NPs (nano-CeO2), with notable performance in various biological tests like redox activity, free radical scavenging, and biofilm inhibition, emerge as significant candidates to address issues in related areas. In this research, copper-decorated nano-CeO2 (Cu@nano-CeO2) were first synthesized and then characterized using advanced techniques such as SEM-EDX, XRD, XPS, BET, and ICP-OES. The biochemical properties of the obtained Cu@nano-CeO2 nanostructure and its performance in polyethersulfone (PES) membranes were thoroughly investigated in this research study. The free radical scavenging effect of Cu@nano-CeO2 at 100 mg/L concentration was determined as 100 % with the same activity as the reference compounds Trolox and ascorbic acid. It enhanced 2.9-fold α-amylase enzyme activity at 50 mg/L. Plasmid DNA was completely degraded at 100 mg/L concentration. Cu@nano-CeO2 provided significant inhibition against tested bacterial and fungal strains, especially Gram-positives than Gram-negatives and fungus. Anti-biofilm activity was determined against S. aureus and P. aeruginosa as 98.3 and 82.1 %, respectively. Furthermore, E. coli inhibition activity of PES/Cu@nano-CeO2 1.0 wt% membrane was determined as 100 %. Owing to the promising results obtained, we can suggest that Cu@nano-CeO2 can be used in wastewater treatment.